Utilization of Corn (Zea Mays) wastes in Bioethanol production by Separate Hydrolysis and Fermentation - Janet Appiah Osei (Center for Science and Technology, IAIN Surakarta, 2021)
The study investigates the feasibility of producing bioethanol from corn (Zea mays) wastes. Corn cobs, husks and grains were collected from Githurai market and analysis was done in the Kenyatta university laboratory. Wastes were physically pre-treated to increase their surface area for enzymatic reactions. Separate Hydrolysis and Fermentation were carried out by using Aspergillus niger for enzymatic hydrolysis and Saccharomyces cerevisiae yeast for fermentation at different incubation temperatures (28oC, 30oC, 32oC) and times (24, 48, 72 and 96 hours). Fermentation was carried out in 150 ml cotton- plugged conical flasks containing 100 ml sample hydrolysates inoculated with 2 ml cultured yeast suspension. Ethanol concentration was determined by potassium dichromate oxidation method after each incubation time and expressed as % v/v whilst ethanol yield (l/kg) was derived from the ethanol concentration divided by the quantity of substrates used. Maximum yields of 1.84 l/kg, 1.76 l/kg and 2.05 l/kg were obtained from 50 g of pre-treated corn cobs, corn husks and corn grains respectively. The optimum temperature for maximum ethanol yield in all corn substrates was 30oC whilst incubation time 96 hours, 48 hours and 24 hours were optimum for ethanol production in corn cobs, corn husks and corn grains respectively. Results show that bioethanol can easily be produced from corn wastes and is recommended that they are used wisely for energy generation specifically bioethanol to add value to them rather than landfilling.